2000
DOI: 10.1099/0022-1317-49-11-985
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of oral isolates of Candida albicans in HIV-positive patients: correlation between candidal carriage, karyotype and disease stage

Abstract: Opportunist infections involving Candida albicans often develop in HIV-positive patients and oral lesions tend to become more frequent as the disease progresses. Previous studies have shown contrasting results concerning the variability of the pulsed-®eld gel electrophoresis (PFGE) subtypes of C. albicans observed in HIV-positive patients. Carriage of C. albicans was determined by an oral rinse technique; 41 strains of C. albicans (78% serotype A and 22% serotype B) were isolated. There was a direct correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…[5][6][7][8][9] Our results are in good agreement with those reported in previous studies on PFGE typing of C. albicans where the karyotype pattern consists mainly of six or seven bands, but more rarely eight bands. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Differences in the patterns obtained may be related to technical variations in PFGE technique used. [7][8][9][10]17 It is important to point out that the number of bands revealed by PFGE does not necessarily correspond to the number of the yeast chromosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] Our results are in good agreement with those reported in previous studies on PFGE typing of C. albicans where the karyotype pattern consists mainly of six or seven bands, but more rarely eight bands. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Differences in the patterns obtained may be related to technical variations in PFGE technique used. [7][8][9][10]17 It is important to point out that the number of bands revealed by PFGE does not necessarily correspond to the number of the yeast chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] Differences in the patterns obtained may be related to technical variations in PFGE technique used. [7][8][9][10]17 It is important to point out that the number of bands revealed by PFGE does not necessarily correspond to the number of the yeast chromosomes. Indeed, homologous chromosomes may migrate separately possibly because of deletion, translocation, insertion of movable DNA or differences in the amount or distribution of repetitive sequences.…”
Section: Discussionmentioning
confidence: 99%
“…One report showed that serotype A was found to be dominant (78% serotype A and 22% serotype B) in strains isolated from the human oral cavity (Capoluongo et al, 2000). Therefore, salivary antibodies induced by tonsillar immunizations of C. albicans ATCC 18804 can be expected to be useful in the prevention of C. albicans infection in most humans.…”
Section: Discussionmentioning
confidence: 99%
“…Capoluongo et al. also reported that Candida colonization intensity increased with the progress of HIV infection and Candida intensity was higher in patients with CD4+ T cell count lower than 200 cells/μL.…”
Section: Candida Colonization and Peripheral Cd4+ T Cell Countmentioning
confidence: 92%
“…Capoluongo et al. observed a strong correlation between the lg cfu/mL of C. albicans and the lg viral load copies/mL ( r = 0.85, p < 0.001).…”
Section: Candida Colonization and Plasma Hiv Rna Levelmentioning
confidence: 97%